Valuably Developed Personality and His/Her Health - Savchin, Myroslav Vasilievich (Psychological Prospects Journal, 2012)
Methodological positions are inlaid for the analysis of vertex levels of development of personality. Integral description of the valuably developed personality is presented, essence of common to all mankind qualities and features of his/her life in the context of maintenance of spiritual, heartfelt and physical health.
Keywords: healthy personality spiritual potential of personality heartfelt potential of personality vital experience life of personality lifestyle common to all mankind personal capabilities